Checklist of the Inland Fishes of El Salvador - Mcmahan, Caleb D.; Matamoros, Wilfredo A.; Álvarez Calderón, Francisco S.; Henríquez, Wendy Yamileth; Recinos, H. Michelle; Chakrabarty, Prosanta; Barraza, Enrique; Herrera, Néstor (Zootaxa, 2013)
The inland fish fauna of El Salvador and its distribution was originally described in 1925 by Samuel Hildebrand. That work has been the main source of information for freshwater fishes of El Salvador up to today. Based on the combination of an intensive literature review, electronic database searches, re-identification of museum specimens, and fieldwork, we hereby provide an updated checklist of the inland fishes of El Salvador. This checklist provides distributional data at the Salvadoran hydrographical and political (by department) levels. The checklist is systematically arranged at the ordinal and familial level and then alphabetically therein. The freshwater fish fauna of El Salvador includes 101 species divided into 64 genera, 29 families, and 14 orders. According to their supposed tolerance to salinity, 73% of these species are peripheral, 23% secondary, and only 4% are primary freshwater fishes. One species is endemic to the country, Amatitlania coatepeque. The low number of primary freshwater fishes and endemics is comparable to the Central American Pacific slope in particular, as well as northern Central America in general.